Front Cover Picture: Stereoselective Synthesis of Hydropyrano[3, 2‐b]indoles via Organocatalytic Asymmetric Inverse‐Electron‐Demand Oxa‐Diels–Alder Reaction (Adv. Synth. Catal. 18/2016). Issue 18 (22nd August 2016) - Yang, Lei; Huang, Wei; He, Xiang‐Hong; Yang, Ming‐Cheng; Li, Xiang; He, Gu; Peng, Cheng; Han, Bo
Abstract : The front cover picture showcases research from the groups of Cheng Peng and Bo Han. Enantio‐ and diastereoselective inverse‐electron‐demand oxa‐Diels–Alder reactions are described between ( Z )‐2‐ylideneoxindoles and aldehydes in the presence of a chiral secondary amine catalyst. Details can be found in the Update on pages 2970–2975 (L. Yang, W. Huang, X.‐H. He, M.‐C. Yang, X. Li, G. He, C. Peng, B. Han, Adv. Synth. Catal .2016, 358, 2970–2975; DOI:10.1002/adsc.201600465 ).